Binderless Briquetting of Mixed Cassava Rhizome, Sugarcane Bagasse, and Sugarcane Straw for Producing Solid Biofuel with High Durability - De Conti, Andrea Cressoni [UNESP]; Granado, Marcos Paulo Patta [UNESP]; Padilla, Elias Ricardo Durango [UNESP]; Nakashima, Gabriela Tami; De Conti, Cláudio [UNESP]; Yamaji, Fábio Minoru (Springer Nature, 2022)
This study aimed at investigating the binderless densification of biomass for the production of a durable solid biofuel by mixing cassava rhizome, sugarcane bagasse, and sugarcane straw. Six different treatments were applied with specific percentages of these three biomass feedstocks for the densification in a lab-scale press with heating of 120 °C. Three blend treatments and three 100% material treatments (without mix) were analyzed. Achieved briquettes were examined via various tests including proximate analysis, volumetric expansion, compression test, and energy index to assess the mechanical and energetic properties. Results indicated that the mixtures are suitable for the production of briquettes and treatment B2 was the best blend for briquette production. This study suggested that binderless densification of biomass can be achieved with the mixing of cassava rhizome, sugarcane bagasse, and sugarcane straw, which will support the development of qualified solid biofuels without the cost of binders.
Keywords: Agriculture; Bioenergy; Biomass; Brazil; Densification; Waste